Numerical and experimental studies of a radial truck tire with tread pattern. (November 2015) - Wang, Wei; Yan, Shan; Zhao, Yayuan
A three-dimensional nonlinear finite element tire model with detailed tread pattern and a smooth tread tire model for comparison are constructed. The tire–rim and tire–road interactions are considered in these tire models. The static vertical loading and rolling procedures of the tire are simulated by using the ABAQUS code. Presented in this paper are the relationship between vertical loading and tire deflection, and the contact footprints, along with the pressure distribution achieved by the pressure-sensing pad experiment and the finite element tire modeling. The predicted results via the modeling method proposed in this study are in good agreement with experiments. In addition, the forces of belts, the deformation and strain energy density of tread blocks obtained from the tire model are also presented when the tire is in braking and traction rolling situations. The reliability of the proposed tire modeling methodology is validated.